Synthesis of non-peripheral phthalocyanine sensitizers and investigation of the effect of ultrasound-light stimulus synergy on singlet oxygen production - Kutlu, Oznur Dulger; Kilicarslan, Fatma Aytan; Erdogmus, Ali (PERGAMON-ELSEVIER SCIENCE LTD, 2024)
The high singlet oxygen production capacity and other unique properties of phthalocyanines allow these compounds to be widely used as sensitizers in photodynamic therapy (PDT) and sonodynamic therapy (SDT) in the treatment of cancer. Sono-photodynamic therapy (SPDT), which uses a combination of light and sound stimulation together and has a very high therapeutic effect compared to PDT, is an increasingly important new method for cancer treatment. Published studies on the application of non-peripherally phthalocyanines in SPDT are limited in the literature. With this in mind, in this study, the synthesis and characterization of novel non- peripherally tetra-substituted (4-tert-butylbenzyl)oxy) tert-butylbenzyl)oxy) metal-free (2), 2 ), Mg(II) (3), 3 ), Zn(II) (4), 4 ), and In(III)CI (5) 5 ) phthalocyanines and their potential as a sono-photosensitizer in SPDT applications as well as PDT applications were determined. Comparative photochemical and sono-photochemical studies showed that the singlet oxygen quantum yields of the synthesised phthalocyanine compounds were calculated as 0.027, 0.22, 0.29 and 0.32 for 2 , 3 , 4 and 5 respectively, by photochemical studies using only light irradiation, while these values increased to 0.11, 0.28, 0.58 and 0.64 for 2 , 3 , 4 and 5 respectively, by sono-photochemical studies after the synergistic effect of light and ultrasound. These results showed that the combined use of ultrasound waves and light as a stimulation method exhibited a more effective therapeutic effect compared to light stimulation alone. According to the singlet oxygen efficiency, it was shown that the presence of a metal ion on the phthalocyanine ring increased the singlet oxygen production in both methods.
Keywords: Phthalocyanines; Sono-photosensitizer; Singlet oxygen; Photo-physicochemical properties; Sono-photodynamic therapy; PHOTODYNAMIC THERAPY; PHOTOSENSITIZERS; PHOTOPHYSICS; ZINC; Chemistry; Crystallography